Pengaruh Work Conflict dan Job Insecurity Terhadap Kepuasan Kerja Karyawan PT Indosat Ooredoo Hutchison - Rahmat, Wan Fauzi Aulia; Sihombing, Marlon (Peneliti.net, 2024)
If human resources experience obstacles in the form of conflicts in the company, then all company activities will also be hampered. However, if the company and human resources can overcome the problem, not only get experience to overcome the problem but all employees who successfully overcome the conflict will also feel job satisfaction. The purpose of this study was to determine the effect of work conflict and job insecurity on the job satisfaction of Indosat Ooredoo Hutchison employees in the Sales Planning And Automation Group. This form of research is quantitative research with an associative approach. The population in this study were all employees of PT Indosat Ooredoo Hutchison in the Sales Planning and Automation Group, totaling 46 employees with sampling techniques using saturated sampling. The sampling technique used is the Saturated Sampling Technique. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that work conflict and job insecurity had a significant effect both partially and simultaneously on the job satisfaction of Indosat Ooredoo Hutchison employees in the Sales Planning And Automation Group, and had an effect of 49.5%, while the remaining 50.4% was influenced by other factors outside this research model.